Cost analysis of variable stiffness composite structures with application to a wind turbine blade. (1st November 2018) - Sohouli, A.; Yildiz, M.; Suleman, A.
Abstract: This paper presents a design framework for cost analysis of a wind turbine blade made of variable stiffness composite laminates. The framework consists of a design optimization, time-variant reliability analysis, structural performance analysis, and life-cycle cost evaluation phases. The objective of the optimization phase is the maximization of the stiffness by searching the optimum values of the design variables. The design variables are piecewise patch orientations and material properties of the fiber reinforced composites. Different volume constraints of carbon fiber reinforced polymer (CFRP) are imposed on composite laminates in the load-carrying component. Next, the structural performance and the service lifetime of the blade designs are estimated based on the time-variant reliability assessment. The time-variant reliability is evaluated using an outcrossing asymptotic method. The wind speed and the material properties are considered, respectively as the random process and the random parameters during the reliability assessment. The maintenance cost of the blade designs is determined by the combination of the estimated structural performance and an analytical method. Finally, the final designs are selected according to the cost-effectiveness values of the designs under the different discount rates and the undiscounted costs.